THE EFFECT OF METHANOL EXTRACT OF Cerbera odollam LEAVES ON LOCOMOTION AND EXPLORATION ACTIVITIES OF Spodoptera frugiperda LARVAE - Subakti Putri, Syifa Nabilah; Susanto, Agus; Bari, Ichsan Nurul (Percetakan Umi Toaha Makassar, 2025)
The fall armyworm (FAW), Spodoptera frugiperda, is one of the major pests of maize, exhibiting high adaptability and causing significant losses to agriculture in Indonesia. An environmentally friendly approach to controlling FAW infestations involves using local toxic plants, such as Cerbera odollam, also known as Bintaro, which contains cardenolide glycosides, saponins, and alkaloids with potential as botanical insecticides. This study aimed to evaluate the effect of the methanol extract of C. odollam leaves on the locomotion and exploration activities of FAW larvae. The test was conducted using the leaf dip method at concentrations of 0, 1000, 2000, and 4000 ppm, with six replications. The samples were then analyzed and observed using the Organism Video Tracking Application ToxTrac v2.96. Results showed that higher extract concentrations led to a decrease in larval speed, from 17.48 mm/s to 1.83 mm/s, and a reduction in exploration area, from 48 to 9. In addition, larval immobility duration (freeze activity) increased nearly sevenfold compared to the control. These findings indicate that C. odollam shows promise as a natural insecticide that repels FAW larvae by limiting their movement and exploratory behavior.